Development of Sustainable Cellulose-Based Tissue Materials Using an Innovative Experimental and Computational Methodology - Morais, Flávia; Carta, Ana; Amaral, Maria; Curto, Joana (KnE Materials Science, 2022)
In recent years, the tissue industry has been exposed to several challenges related to the growing demand for high-quality materials and sustainability. An approach that combined experimental and computational planning was implemented and presented in this work. For this purpose, a simulator that established relationships between the key fibre properties, the process steps that modify them, and the functional properties, named the SimTissue, was developed and validated. Different scenarios and a summary of the SimTissue research strategy are presented. The experimental planning design consisted of examining the influence of refining, enzymatic treatment, and incorporation of additives such as micro / nanofibrillated cellulose and biopolymers. The correlations between these tissue process inputs, and the softness, strength and absorption properties were established using the SimTissue. Overall, the SimTissue predicted and optimized several case studies for the management and optimization of sustainability formulations. Keywords: 3D computational simulation, cellulose-based materials, furnish optimization, tissue materials